Design and Testing of 2 Novel Scores That Predict Global Sagittal Alignment Utilizing Cervical or Lumbar Plain Radiographs. Issue 2 (February 2018) - Goldschmidt, Ezequiel; Angriman, Federico; Ferreyro, Bruno; Agarwal, Nitin; Zhou, James; Chen, Katherine; Tempel, Zachary J; Gerszten, Peter C; Kanter, Adam S; Okonkwo, David O; Passias, Peter; Scheer, Justin; et al.
Abstract : BACKGROUND : Global sagittal deformity is an established cause of disability. However, measurements of sagittal alignment are often ignored when patients present with symptoms localizing to the cervical or lumbar spine. OBJECTIVE : To develop scoring scales to predict the risk of sagittal malalignment in patients with only cervical or lumbar spine radiographs. METHODS : A retrospective review of a prospectively maintained multicenter adult spinal deformity database was performed. Primary outcome (sagittal malalignment) was defined as a C7 plumbline ≥ 50 mm. Two multivariate logistic regressions were performed using patient characteristics and measurements derived from cervical or lumbar radiographs as covariates. Point scores were assigned to age, body mass index (BMI), and lumbar lordosis or T1 slope by rounding their β coefficients to the nearest integer. RESULTS : Nine hundred seventy‐nine patients were included, with 652 randomly assigned to the derivation cohort (used to build the score) and 327 comprising the validation set. Final cervical score for the primary outcome included BMI ≥ 25 (1 point), age ≥ 55 yr (2 points), and T1 slope ≥ 27 o (2 points). Final lumbar score for the primary outcome included BMI ≥ 25 (1 point), age ≥ 55 yr (1 point), and lumbar lordosis ≥ 45 o (-1 points). High scores for both the cervical and lumbar spine presented with high specificity and positive likelihood ratios of sagittal malalignment. CONCLUSION : We developed scoring scales to predict global sagittal malalignment utilizing clinical covariates and cervical or lumbar radiographs. Patients with high scores may prompt imaging with long‐cassette plain films to evaluate for global sagittal imbalance.